Pharmaceutical care for patients with diabetes mellitus in the unified health system (SUS): integrative review (Research, Society and Development, 2022)
Brazil is the 6th country with the highest incidence of diabetes in the world, with 15.7 million people with the disease. Diabetes mellitus (DM) is a syndrome of metabolism, of multiple origin, due to the lack of insulin adequately exerting its effects. We have several types of diabetes such as type 1 diabetes mellitus, type 2 and gestational diabetes. This study will address the benefits of pharmaceutical care for diabetic patients. Aiming to demonstrate the importance of the pharmacist in performing pharmacotherapeutic follow-up to patients with diabetes mellitus, with the purpose of evaluating the patient, the use of medications, which are used so that they do not have drug interactions in order to ensure excellent results in pharmacotherapy and blood glucose control, bringing improvement in quality of life of the patient. The study is an integrative review of the literature, articles published between the years 2017 to 2022, comprising a period of five years. The search for the articles was carried out in the databases Pubmed, Scielo, Medline, Google academic and also in journals that published on the subject pharmaceutical care to patients with diabetes mellitus. After the research we observed that the pharmacist assists in several problems related to therapy, so the role of the pharmaceutical professional is indispensable in the follow-up of patients with diabetes, where it brings benefits to the patient, aiming at improving pharmacotherapy, guiding the patient on glycemic control, avoiding drug interactions and the possible effects that diabetes mellitus can bring to the patient.